Self-tuning fuzzy pid control PF hydro-diffusion essential oil extraction system / Zakiah Mohd Yusoff - Mohd Yusoff, Zakiah (Institute of Graduate Studies, UiTM, 2014)
Essential oils (EO) is a substance extracted from a botanical material and always in high demanded. Steam distillation is a widespread method to isolate the essential oil from aromatic plants. The steam distillation method is most preferable due to factors of operational cost, cleanliness, system cost, high productivity and maintenance cost. However, some disadvantages of this method is loss of some volatile compounds, which will be diluted with boiling water within the distillation tank. The issue of steam distillation has not been given sufficient treatment in literature. The hydro-diffusion system was implemented as a viable alternative to overcome these setback. In the extraction process, the temperature will influence the final product of the extraction.